Cyber warfare and cyber terrorism - Janczewski 1943-; Colarik (Information Science Reference, 2008)
"This book reviews problems, issues, and presentations of the newest research in the field of cyberwarfare and cyberterrorism. While enormous efficiencies have been gained as a result of computers and telecommunications technologies, use of these systems and networks translates into a major concentration of information resources, createing a vulnerability to a host of attacks and exploitations"--Provided by publisher.